التعاون الدولي في مكافحة الإرهاب في النظام السعودي والفقه الإسلامي والاتفاقيات الدولية - الشهراني، سلطان بن محمد بن عبدالله آل موسي (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2019)
لخص في التعرف على مفهوم التعاون الدولي في اللغة والنظام والنظام السعودي والفقه الإسلامي وتعريف جرائم الإرهاب في اللغة والنظام السعودي والفقه الإسلامي وما هو دور التعاون الدولي في مكافحة الإرهاب في النظام السعودي والفقه الإسلامي من خلال الاتفاقيات الدولية الجماعية والثنائية. أهداف البحث: 1-التعرف على مفهوم التعاون الدولي. 2-تحديد مفهوم مصطلح الجرائم الإرهابية. 3-ما هو دور التعاون الدولي في مكافحة الإرهاب في النظام السعودي والفقه الإسلامي. 4-ما هو دور الاتفاقيات الدولية في مكافحة الإرهاب. المنهج المتبع في البحث: المنهج التحليلي الاستقرائي. النتائج 1-يعرف التعاون الدولي بأنه طريقة من طرق العلاقات الدولية تهدف إلى تنفيذ سياسة محددة خلال فترة زمنية معينة في مجال أو عدة مجالات " 2-مجالات التعاون الدولي تتمثل في ثلاثة عناصر: 1-التعاون الدولي في مكافحة جرائم الإرهاب. 2-التعاون الدولي الأمني لتسليم المجرمين. 3-التعاون القضائي. التوصيات: 1-تعزيز فكرة التعاون الدولي في الجرائم الإرهابية حتى يستطيع المجتمع الدولي القضاء على هذه الآفة الخطيرة. 2-عقد مؤتمرات وندوات ولقاءات بين جميع الدول المعنية بمكافحة الإرهاب حتى تستطيع الآليات لمكافحة هذه الظاهرة. 3-مد يد العون والمساعدة من الدول الغنية إلى دول المواجهة للقضاء على الفكر المتطرف.
The research summarizes the definition of the concept of international cooperation in the language and the system and the Saudi system and Islamic jurisprudence and the definition of crimes of terrorism in the language and the Saudi system and Islamic jurisprudence and what is the role of international cooperation in the fight against terrorism in the Saudi system and Islamic jurisprudence through international collective agreements and bilateral. Research goals: 1. Identify the concept of international cooperation. 2. Defining the concept of the term terrorist crimes. 3- What is the role of international cooperation in combating terrorism in the Saudi system and Islamic jurisprudence? 4- What is the role of international conventions in the fight against terrorism. Research Methodology: Inductive analytical approach Results 1. International cooperation is defined as a method of international relations aimed at the implementation of a specific policy within a certain period of time in one or several areas. 2. The areas of international cooperation are three elements: International cooperation in combating terrorism crimes. 2. International security cooperation for extradition. 3. Judicial cooperation. Recommendations: 1. Promote the idea of international cooperation in terrorist crimes so that the international community can eliminate this dangerous scourge. 2- Holding conferences, seminars and meetings between all countries concerned with combating terrorism so that mechanisms can combat this phenomenon. 3- Extending a helping hand and help from rich countries to the frontline countries to eliminate extremist thought.
Keywords: الاتفاقيات الدولية -- الفقه الإسلامي -- جرائم الإرهاب -- التعاون القضائي